Die Rekonstruktion der ’Beißergruppe’ und das Motiv der knöchelspielenden Kinder - Meinecke, Katharina; Langendorf, Alarich (Römische Mitteilungen, 2024)
The fragmentary ‘Biter Group’ in the British Museum in London, which shows a boy sitting on the ground and biting another person’s arm, has long been identified as a Hellenistic genre sculpture of two boys quarreling over a game of knucklebones. Based on a personal visual inspection of the original sculpture and an iconographical survey of the motif of children playing with knucklebones, this article proposes a new digital 3D reconstruction for the missing figure of the bitten boy. After producing a photogrammetric image of the sculpture using image-based modeling (IbM), a simplified base mesh of a juvenile male figure was used to reconstruct the bitten boy. This method allows one to easily test different postures for the missing figure and to try out different viewing perspectives and so formulate a possible composition for the whole group.